Impact of Liability to Periodontitis on Glycemic Control and Type II Diabetes Risk: A Mendelian Randomization Study - Shah, Parth D.; Schooling, C. M.; Borrell, Luisa N. (Frontiers in Genetics, 2021)
While the association of periodontitis with Type II diabetes (T2DM) is well-established, the causal relationship remains uncertain. We examined the causal association of periodontitis with glycemic traits (HbA1c, fasting glucose and fasting insulin) and T2DM using Mendelian randomization taking advantage of large genome wide association studies of European and East Asian adults, i.e., the UK biobank (n ≈350,000) (HbA1c), trans-ancestral MAGIC (HbA1c, fasting glucose and insulin), and DIAMANTE (74,124 cases/824,006 controls) and AGEN for T2DM in Europeans and East-Asians, respectively. Periodontitis was instrumented using single nucleotide polymorphisms (SNPs), strongly and independently predicting liability to periodontitis in each ancestry group. SNP-specific Wald estimates were combined using inverse variance weighting. Sensitivity analyses were performed using the weighted median and MR-Egger with meta-analysis of MR estimates for Europeans and East-Asians. Genetically instrumented liability to periodontitis was not associated with glycemic traits or T2DM in either ancestry nor when ancestry specific estimates were meta-analyzed. Our findings do not support a causal association of liability to periodontitis with glycemic traits or T2DM. However, further investigation, using stronger instruments for periodontitis is needed to exclude the possibility of liability to periodontitis playing a role.